Diagnosis of yam viruses - Hughes, J.; Dongo, L.; Ng, S.Y.C. (1998)
Diagnosis of virus diseases of yams at the International Institute of Tropical Agriculture (IITA) is based on the use of indicator plants, insect vectors, serological diagnostics, and electron microscopy (EM). Yam I (YVI), yam mosaic (YMV), and Dioscorea dumetorum (DdV) potyviruses even in mixed virus infection. Yam mosaic virus is mechanically transmissible to Nicotiana benthamiana and YVI is vector-transmissible to Vigna unguiculata. The three viruses can be visualised by EM and their identities confirmed serologically. Dioscorea alata badnavirus (DaV) can be graft-transmitted to V, unguiculata and its presence confirmed by EM and serology, Cucumber mosaic cucumovirus (CMV), reported to occur in yams in West is readily mechanically transmissible to a range of indicator plants and can be detected serologically. Other isometric viruses have recently been found in Nigeria, and these can be isolated and differentiated by mechanical and vector transmission to indicator plants. These diagnostic techniques have enabled initiation of surveys of viruses of Dioscorea spp. in West Africa and substantial progress has been made on the production of virus-tested planting material for international distribution.